Factors Affecting the Performance of Commercial Banks in Indonesia - Iqbal Akbari, Mohamad; Binti Md Yusoff, Siti Khalidah; Azam, Ferdous (Green Publisher Indonesia, 2025)
The performance of commercial banks in Indonesia is influenced by various internal and external factors that reflect the stability and efficiency of the banking industry. This study aims to analyze how these factors affect the performance of commercial banks in Indonesia, which is a crucial sector in the national financial system. This study uses quantitative research methods. The data were obtained in this analysis from every Commercial bank' Quarterly Report. Documents are recorded based on this data form technique through documentation. The collected data were then analyzed by multiple linear regression using E-views 10.0. The results of panel data regression show that all independent variables (bank size, inflation, gross domestic product, operating expenses and operating income, and credit risk) have a significant effect on the dependent variable (performance). All independent variables have an influence of 97.70% on the dependent variable Performance in commercial banks in Indonesia. Then, the remaining 2.30% is influenced by other variables not included in this study. Furthermore, the relationship between Credit Risk, Gross Domestic Product (GDP), and Operating Expenses and Operating Income (BOPO) on Performance has a positive and significant effect. However, the variables Bank Size and Inflation have a significant and negative effect on Performance.